INTEGRASI KESEHATAN MENTAL DALAM PELAYANAN PRAKONSEPSI: SCOPING REVIEW MENGENAI MODEL PELAYANAN, STRATEGI SKRINING, PERAN BIDAN, DAN HAMBATAN IMPLEMENTASI - Rohani; Vera Yuanita (LPPM STIKes Mitra Adiguna, 2026)
Mental health during the preconception period is an essential component of reproductive health that influences pregnancy preparedness and maternal and child outcomes. However, preconception care continues to focus primarily on physical health, and the integration of mental health has not yet been optimally implemented. This scoping review aimed to map the scientific evidence on models of mental health integration in preconception care, screening strategies, the role of midwives, and implementation barriers. A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology and reported in accordance with the PRISMA-ScR guidelines. Literature searches were performed in PubMed, ScienceDirect, Wiley Online Library, Google Scholar, and Research Rabbit. Of the 209 records identified, seven studies met the inclusion criteria and were analyzed using thematic synthesis. Five major themes were identified: models of integrated care, mental health screening strategies, the role of midwives, implementation barriers, and implementation facilitators. The integrated care model emphasized a holistic approach incorporating biopsychosocial assessment, mental health screening, intervention, referral, and follow-up. Midwives were found to play key roles in mental health promotion, early detection, basic counseling, referral coordination, and follow-up. The main implementation barriers included stigma, limited healthcare providers' competencies, the absence of operational guidelines, and weak referral systems. Integrating mental health into preconception care requires a structured, collaborative, and woman-centered approach supported by appropriate policies, enhanced midwifery competencies, and strengthened healthcare systems to improve the quality of preconception services.